Sociopathic Personality Disorder in Humbert Humbertâs Character of Nabokovâs Lolita - Wirawan, Alifiadita Nindyarini; Samanik, Samanik (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Every literary work has its own uniqueness in portraying certain societyâs phenomenon. It can be seen from the creation of a literary work has correlation with the society phenomenon from the elements inside the literary work, like characters and characterization, theme, setting and plot are created. Pickering and Hoeper (1981) stated that the creation of literature is a uniquely human activity, born of manâs timeless desire to understand, express, and finally share experience. Basically, the essence of literary work is where the literary work is used as portrayal media to portrayed or described certain phenomenon in society in which every phenomena has its own story and it become the uniqueness of the literary work. As well as a literary work able to be used to describe certain way of peopleâs thinking and behaviors in particular place and condition which is also add the interesting value of the work itself. In this respect, the writer select one of popular literary works in the world entitled Lolita. This research paper aims to investigate a Russian literary work, whether or not Humbert Humbert character of Nabokovâs Lolita suffer sociopathic personality disorder. By collecting data in form of quotation, statements in the novel and relevant science about the theory of personality disorder particularly sociopathic personality disorder from many sources will reveal the prove that Humbert Humbert is a sociopath in the form of symptoms and characteristic of sociopathic personality disorder. In addition, the paper also analyzes the cause and the impact of sociopathic personality disorder in Humbert Humbert character. The researcher use a sociopathic personality disorder theory by Hare (1997), Loewen (2013), Birnbaum (1910), Yildrim & Dderksen (2013) and psychology of literature approach by Rivaldy (2007)Â  in analyzing the paper. The researcher uses the novel as primary data and relevant journals as the secondary data. Moreover, by using relevant previous studies from many researchers will support the research as well as in gaining precise result of the research itself. The finding of this study are (1) The Symptoms of Sociopathic Personality Disorder; (2) The Characteristics of Sociopath;Â  (3) The Cause of Sociopathic Personality Disorder and (4) The Impact of Sociopathic Personality Disorder toward Humbert Humbert Character in Lolita.